Belvedere glacier. Monte Rosa, Italian Alps : tongue thickness and volume variations in the second half of the 20th century - G. Diolaiuti; C. D'Agata; C. Smiraglia (University of Colorado, 2003)
In studying the response of alpine glaciers to climate warming, the study of debris-covered glaciers is important in order to demonstrate that a negative feedback exists in the temperature-ablation relationship that is introduced by the increase in debris cover. In this paper, variations in the Belvedere Glacier tongue volume and thickness were quantified through a comparison of large-scale maps for 1957 and 1991. A volume increase of 22.7 million m 3 was revealed, and there was a mean increase of 15 m in thickness. Thickening was greatest above 1830 m, and thinning occurred at the glacier front (1830-1770 m). The glacier terminus advanced only slightly. This particular evolution of the Belvedere tongue has been attributed to positive balances of the glacier created by favorable climatic conditions (increase in winter precipitation between the early 1970s and mid-1980s and lower summer temperatures in the 1960s and 1970s). After the mid-1980s, reduced precipitation and a simultaneous increase in temperatures led to a slight retreat of the glacier front in the early 1990s. However, these climatic conditions were not sufficient to bring about a significant reduction of the thickness of the glacier, partly owing to the debris cover, which reduced the role of ablation.